Study the Effect of the Homemade Nitrogen Laser System in Medical Field - B. Mohammed, Saif; M. Najim, Jassim; N. Mohameed, Akram (Iraqi Journal of Science, 2021)
A high power N2 laser of the three stage-Blumlein circuit designed, which consist two identical electrodes, four capacitors and three spark gaps which designed discharge geometry with minimum inductance. This system gives a maximum energy 18 mJ with a pulse time 6.65 ns and wave length 337.1 nm. The distance between spark gap terminals has large effect on the output energy. The ideal distance were 11 mm between the terminals for the first spark gap and 4 mm between the terminals for the second spark gap, the distance between the terminals of the spark gaps has a significant effect on the resulting energy, where the energy decreases when the distance between the terminals of the first and second spark gaps exceeds or Less than from the optimum distances. The effect of N2 laser on the viability of Staphylococcus that isolated from wounds, the samples of bacteria were irradiated with 337.1 nm .N2 laser using 10 pulses/second repetition rates at 10,15 minutes exposure times. The results showed that the viability of bacteria decreased with increasing the exposure time to N2 laser.